Mr. Starbene e il Club dei Vincenti: assessing an anti-smoking campaign for school children (Italian Journal of Public Health, 2008)
Background: People start smoking during childhood and adolescence and the age at which children start smoking is gradually falling: in 2005, it rose to 3.3% in the 11-to-14 year age group whereas in 2002 it was only 1.4% in the same age group.Methods: “Mr Starbene e il Club dei Vincenti”, part of a regional program, Liberi dal Fumo, was assessed through an experimental non-randomized study, by involving parents and teachers, using short questionnaires. The project’s objective was orienting fourth and fifth grade children towards a no-smoking lifestyle. The enrolled population was composed of 5,552 students in the treatment group and 4,758 controls.Results:: after two years, the number of children who had tried smoking but no longer smoked at the moment decreased by 16.3% in the treatment group, while it increased by 12.5% in the controls (p=0.000). The number of children who considered smoking a few cigarettes/day dangerous was higher in the treatment group (+8%) than in the controls (+4.4%) which suggests significant results vis-à-vis perceived smoking hazards. Children who claimed they would not smoke in the future decreased by 57.1% in the treated group as compared with a 21.4% reduction in the control group (p
Keywords: Cigarette smoking; adolescents; primary school; prevention